2018
DOI: 10.1177/1524838018801330
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Male-Targeted Sexual Assault Prevention Programs: A Meta-Analysis

Abstract: According to Black et al., one in five women will be raped during their lifetimes. In one national survey, it was found that of 14,989 female college students from nine institutions, 34% reported experiencing a completed or attempted sexual assault in their lifetimes and 21% of them reported that they had experienced a completed or attempted sexual assault as a college student. Therefore, effective sexual assault prevention efforts targeted at men are needed, and several initiatives have been developed. The cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 40 publications
0
40
0
Order By: Relevance
“…These studies have aimed to change social norms condoning the use of coercive tactics and correcting men’s misperceptions of their peers’ acceptance of sexual violence (e.g., Dardis et al, 2016 ), changing attitudes minimizing or denying rape ( Senn et al, 2017 ), and promoting risk perception and knowledge as well as self-efficacy regarding effective resistance in an assault situation (e.g., Senn et al, 2017 ). However, a recent meta-analysis of sexual assault prevention measures directed at men concluded that there was no evidence of a significant effect across 25 studies in changing attitudes related to sexual assault through intervention efforts ( Wright et al, 2018 ). Thus, there is a need for further studies showing that cognitions and attitudes related to sexual aggression victimization and perpetration may be changed by theory-based treatment efforts.…”
mentioning
confidence: 99%
“…These studies have aimed to change social norms condoning the use of coercive tactics and correcting men’s misperceptions of their peers’ acceptance of sexual violence (e.g., Dardis et al, 2016 ), changing attitudes minimizing or denying rape ( Senn et al, 2017 ), and promoting risk perception and knowledge as well as self-efficacy regarding effective resistance in an assault situation (e.g., Senn et al, 2017 ). However, a recent meta-analysis of sexual assault prevention measures directed at men concluded that there was no evidence of a significant effect across 25 studies in changing attitudes related to sexual assault through intervention efforts ( Wright et al, 2018 ). Thus, there is a need for further studies showing that cognitions and attitudes related to sexual aggression victimization and perpetration may be changed by theory-based treatment efforts.…”
mentioning
confidence: 99%
“…Rather, rape myths are the logic with which truth is established, and are part of the cultural scaffolding which genders the notion of truth, and holds women to a hypothetical ideal which all behavior is measured against, as drawing on MacKinnon’s notion of the “legally perfect rape” (1989). This, therefore, suggests that the way to counteract these attitudes may not lie in interventions on an individual level, as they will have limited effectiveness ( Wright et al, 2018 ). Rather, this would suggest that aggressively sexist attitudes will need to be targeted on a broader level, through re-defining the general cultural and legal landscape, which may in some instanced perpetuate present inequalities ( Kennedy, 2011 ; MacKinnon, 1989 ; Smith, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to increased access to EC over the counter, the growth of SANE programs, and the presence of SANEs in EDs, as well as shifts in the focus of the literatures on sexual assault and EC. Indeed, a brief examination of recent publications on sexual assault reveals a greater focus on risk factors, prevention, and the utilization and efficacy of SANEs who are often based in specific SANE or rape crisis centers outside of EDs (ACOG, 2009; 2015, 2017; Bird, Gilmore, George, & Lewis, 2016; Fok & Blumenthal, 2016; Mellins et al, 2017; Montanari Vergallo, Zaami, Di Luca, & Marinelli, 2017; Shen, Che, Showell, Chen, & Cheng, 2017; Vrees, 2017; Wright, Zounlome, & Whiston, 2018), whereas the EC literature has focused on general access and the mechanisms of action and efficacy of EC. Additionally, our scoping review included articles with diverse study designs, and the response rates ranged from poor to average.…”
Section: Discussionmentioning
confidence: 99%